2016
DOI: 10.1515/raon-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in segregation genes BUB1B and TTK and gastric cancer risk

Abstract: BackgroundMalignant transformation of normal gastric cells is a complex and multistep process, resulting in development of heterogeneous tumours. Susceptible genetic background, accumulation of genetic changes, and environmental factors play an important role in gastric carcinogenesis. Single nucleotide polymorphisms (SNPs) in mitotic segregation genes could be responsible for inducing the slow process of accumulation of genetic changes, leading to genome instability.Patients and methodsWe performed a case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) encodes a kinase participating in the spindle checkpoint; this protein plays a critical role in the inhibition of the anaphase-promoting complex/cyclosome (APC/C) and functions in delaying the onset of anaphase and ensuring proper chromosome segregation [42]. The oncogene role of BUB1B has been observed in cancers such as prostate cancer, glioblastoma and gastric cancer [43][44][45]. BUB1B is overexpressed in breast cancer, and the level of BUB1B mRNA is significantly correlated with intrachromosomal instability [46].…”
Section: Discussionmentioning
confidence: 99%
“…BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) encodes a kinase participating in the spindle checkpoint; this protein plays a critical role in the inhibition of the anaphase-promoting complex/cyclosome (APC/C) and functions in delaying the onset of anaphase and ensuring proper chromosome segregation [42]. The oncogene role of BUB1B has been observed in cancers such as prostate cancer, glioblastoma and gastric cancer [43][44][45]. BUB1B is overexpressed in breast cancer, and the level of BUB1B mRNA is significantly correlated with intrachromosomal instability [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have proven the role of BUB1B in cancers. BUB1B may contribute to gastric tumorigenesis and the risk of tumor development [ 15 ]. Overexpression of BUB1B in prostate cancer cells promotes cell proliferation and migration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variants were associated with reduced risk for the development of diffuse type, increased survival, and decreased probability for the development of poorly differentiated adenocarcinoma [Bao et al, ]. Two previous studies also revealed significant associations between genotypes of rs758099 in mitotic kinase AURKC and rs151658 in mitotic kinase TTK and histopathological variables of patients, including Lauren classification and the degree of differentiation [Hudler et al, ; Mesic et al, ].…”
Section: Discussionmentioning
confidence: 99%